Application of Ultrasonic Waves for Examination of Damascus and Bulat Steel - Sidorenko, Irina G.; Durukan, Yasemin; Teplyakova, Aleksandra V. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2021)
Methods for determining of material of a museum object made of Damascus and Bulat steel by non-destructive ultrasonic methods are considered. A model of the Bulat steel structure is proposed and a method for evaluating of metal parameters is developed. A combination of spectral characteristics of repeatedly reflected signals and speed of ultrasonic waves propagation is proposed as informative parameters based on experimental studies.